Breeding Unity: Battlestar Galactica's Biracial Reproductive Futurity. - Kustritz, Anne (Camera Obscura, 2012)
The article discusses the theme of eugenics in the science fiction television series "Battlestar Galactica." The author argues that the series, which lacks queer characters, envisions the future in terms of purely heterosexual biracial reproduction, tying the human specie's survival to the selection of children with ideal genetics.